Desain dan Manufaktur Sistem Pemberian Pakan Ikan Otomatis Berbasis IoT dengan Mikrocontroller ESP32 dan Integrasi Tenaga Surya - Irawan, Hery; Suryowinoto, Andy; Broto Sasongko, Sukendro; Widianto, Angger Eka (Rekayasa Material, Manufaktur dan Energi, 2026)
Fish farming in Indonesia has significant potential, both for consumption and ornamental purposes. However, one of the main challenges in fish farming is the manual feeding process, which is time-consuming and requires considerable labor. To address this issue, this research develops an automated fish feeding device based on the Internet of Things (IoT). This study aims to design and test an automatic fish feeding device that uses the ESP32 microcontroller connected to IoT. The system allows for automatic and controlled feeding, based on time settings and the required amount of feed. The methods employed in this research include the design of hardware and software integrated with IoT sensors, which can be programmed to dispense feed at specific distances and times. Testing was conducted to measure feed dispensing distance, energy efficiency, and labor cost savings. The test results indicate that the device is capable of dispensing feed up to a distance of 5 meters, with feed particle sizes ranging from 4-5 mm and the motor running at 12,000 rpm. The system also utilizes solar panels as an energy source, reducing dependence on electricity. The findings of this study demonstrate that the IoT-based automatic feeding device can enhance operational efficiency, reduce labor costs, and decrease electricity consumption, making it an innovative solution suitable for the fish farming industry in Indonesia.